Implementasi Kreativitas Pada Ekstrakurikuler Aeromodelling(Studi Kasus di SMK Bina Dhirgantara ColomaduKabupaten Karanganyar Tahun Pelajaran2014/2015) - Riyana, Susan (2016)
his research aimed at describing the form of creativity implementation through extracurriculara eromodelling atSMK Bina Dhirgantara Colomadu, Karanganyar Regency, in The Academic Year of 2014/2015, describing the obstacles of creativity implementation through extracurricular aeromodelling at SMK Bina Dhirgantara Colomadu, Karanganyar Regency, in The Academic Year of2014/2015, describing the solutions to solve the obstaclesof creativity implementation through extracurricular aeromodelling at SMK Bina Dhirgantara Colomadu, Karanganyar Regency, in The Academic Year of 2014/2015. The type of this research is descriptive qualitative. The Subjects of this research are headmasters, trainers of aeromodelling and students of SMK Bina Dhirgantara in The Academic Year of2014/2015. The objectin this research is creativity. The technique of data collection in this research is interactive including observation, interviewand documenta tion. The tecnique ofdata validity in this research is using two kinds oftriangulation, they are: triangulation of data collection technique and triangula tion of data source. The results of this research can be concluded that: 1) The form ofimplementation of creativity through extracurricular aeromodelling atSMK Bina Dhirgantara Colomadu, Karanganyar Regency in The Academic Year of 2014/2015 had high motivation, high involvement, big curiosity, high diligence, andtendency of not being easily satisfied withthe work achievement, 2) The obstacles of implementation through extracurricular aeromodelling at SMK Bina Dhirgantara Colomadu, Karanganyar Regency in The Academic Year of2014/2015 were: the students felt bored with the monotonous activity and learning environment, the students had passive behavior and laziness, the students had character of being easily hopeless, the students had been satisfied enough withthe standars given by the teachers. 3) The solutions to solve the obstacles of creativity implementation through extracurricular aeromodelling at SMK Bina Dhirgantara Colomadu, Karanganyar Regency in The Academic Year of 2014/2015 were: creating a new learning atmosphere, giving opportunity to the passive students to do the tasks or homeworks that must be done seriously willingly or unwillingly, the trainer gives an opportunity to ask question for the students after the trainer explaines theory or practice, giving motivation to the students who had no hard-work mentality during the activity of aeromodeling, the trainer gives the design examples of creative aeroplane replica in order that the passive students are interested in the learning.